Application of expanded noninvasive prenatal test in prenatal diagnosis of fetuses with increased nuchal translucency. (12th December 2022) - Xie, Xiaoxiao; Zhou, Honghui; Zhao, Qingdong; Lu, Yanping; Meng, Yuanguang
Abstract: Objectives: To investigate the efficiency of the upgraded noninvasive prenatal test (NIPT-Plus) in fetuses with increased nuchal translucency (NT). Methods: Fetuses with an increased NT at or above 2.5 mm were selected for prenatal diagnosis. Amniotic fluid was collected from all cases for karyotype analysis and copy number variation sequencing (CNV-seq), and cell-free fetal DNA (cfDNA) in maternal blood was tested using Noninvasive Prenatal Test (NIPT-Plus) before amniocentesis in some cases. The results of amniocentesis with different NT thicknesses were analyzed and compared with those of NIPT-Plus. Results: A total of 125 eligible patients were divided into group A (2.5 mm ≤ NT < 3.0 mm) and group B (NT ≥ 3.0 mm). In group A, the detection rate of chromosomal aneuploidy and pathogenic copy number variation (CNV) was 10.6% and 6.4%, respectively. The total chromosome abnormality rate in group B (34.7%) was significantly higher than that in group A (17%). In 72 patients who underwent NIPT-Plus and amniocentesis, chromosomal aneuploidy accounted for 80.8% of the total chromosomal abnormalities. Among 21 cases of chromosomal aneuploidy, NIPT-Plus detected 20 cases. The sensitivity and specificity of NIPT-Plus toward aneuploidy detection were 95.2% and 100%, respectively. Among the five cases of pathogenic CNV, only two were detected using NIPT-Plus. Conclusion: NIPT-plus is recommended as the first choice for fetal diagnosis in pregnant women with 2.5 mm ≤ NT < 3.0 mm who do not accept invasive prenatal diagnosis. When NT ≥ 3.0 mm and NIPT-Plus detects chromosomal aneuploidy, a rapid prenatal diagnosis can be performed through amniocentesis. In cases where NIPT-Plus yields negative results, amniocentesis still needs to be performed to detect chromosome microdeletions/duplications in order to avoid a missed diagnosis.